On the influence of grain boundary misorientation on the severe plastic deformation of aluminum bicrystals : a three-dimensional crystal plasticity finite element method study - Liu, Mao (2021)
A three-dimensional crystal plasticity finite element method model is developed to investigate the influence of the grain boundary (GB) misorientation on the equal-channel angular pressing deformation of aluminum bicrystals. Aluminum bicrystals with symmetric 〈112〉 tilt boundaries and misorientations of 9 deg (low angle), 15 deg (transitional), and 30 deg (high angle) have been designed to study the influence of GB misorientations on the deformed areas near GBs. The numerical results indicate that a high-angle grain boundary acts as a barrier in terms of Mises stress distribution, plastic slip, and lattice rotation, while the aluminum bicrystal with low-angle grain boundary still behaves similarly to a single crystal. An intermediate configuration is found for the aluminum bicrystal with transitional grain boundary. It is also found that the geometry of the GB after deformation depends on the initial orientation of the grain at the lower part of the billet.